Valorisation of the invasive species, Prosopis juliflora, using the carboxylate platform to produce volatile fatty acids. (September 2019) - Njokweni, Sesethu G.; Weimer, Paul J.; Warburg, Lisa; Botes, Marelize; van Zyl, Willem H.
Highlights: Prosopis juliflora has low NDF levels but high ADF which restricts digestibility. Non-sterile fermentation conditions were used with no pH control or added nutrients. Average VFA chain lengths ranged from 2.71 to 2.86. 72-h batch fermentation yielded 8.8–9.9 mmol of alkyl groups per gram of substrate. Abstract: Biomass derived from low-value, high-volume invasive plant species is an attractive, alternative feedstock to produce biofuels and biochemicals. This study aimed to use the carboxylate platform to valorize the invasive leguminous shrub, Prosopis juliflora (Mesquite), by utilizing in vitro rumen fermentations without chemical pretreatment to produce volatile fatty acids. The three fractions of the mesquite: leaves (ProL), stems (ProS) and branches (ProB) were compared regarding chemical composition, neutral detergent fiber (NDF) digestibility at 7 time points and VFA production after 72 h with sugarcane bagasse (SCB) as a reference. NDF digestibility was significantly ( P < 0.05) higher in ProL (35.8%) than ProS (30.4%) and ProB (20.9%) compared to SCB (21.9%). VFA concentrations from 20 g biomass L −1 showed significant differences with 8.07, 6.71 and 6.51 g L −1 for ProL, ProS and ProB respectively, while SCB yielded 4.02 g L −1 . These concentrations were comparable with other platforms that employ chemically pretreated biomass for VFA production.